Market Strategy Analysis of Li Ning Based on SWOT and 4PS - Deng, Xiyu (Transactions on Social Science, Education and Humanities Research, 2024)
With the advent of the 21st century, the world economy is getting better and better, and people pay more attention to health and vigorously develop sports. With the tide of The Times, the development of sports companies is also getting better and better. This paper mainly discusses the market analysis of Li Ning Company. After years of development, Li Ning company, as a leading brand in China’s sports industry, has shown a strong momentum of development in the market research. But at the same time, Li Ning also needs to constantly adjust and optimize our marketing operation and marketing strategy to achieve sustainable development. Li Ning’s market research will be very helpful to other participants in the Chinese sports market to better understand the development of the market development trend and the internal needs of consumers and to develop more critical market strategies and product planning, to occupy a dominant position in the fierce market competition.